The Partner Switching System of the SigF Sigma Factor in Mycobacterium smegmatis and Induction of the SigF Regulon Under Respiration-Inhibitory Conditions - Oh, Yuna; Song, Su-Yeon; Kim, Hye-Jun; Han, Gil; Hwang, Jihwan; Kang, Ho-Young; Oh, Jeong-Il (Frontiers in Microbiology, 2020)
The partner switching system (PSS) of the SigF regulatory pathway in Mycobacterium smegmatis has been previously demonstrated to include the anti-sigma factor RsbW (MSMEG_1803) and two anti-sigma factor antagonists RsfA and RsfB. In this study, we further characterized two additional RsbW homologs and revealed the distinct roles of three RsbW homologs [RsbW1 (MSMEG_1803), RsbW2 (MSMEG_6129), and RsbW3 (MSMEG_1787)] in the SigF PSS. RsbW1 and RsbW2 serve as the anti-sigma factor of SigF and the protein kinase phosphorylating RsfB, respectively, while RsbW3 functions as an anti-SigF antagonist through its protein interaction with RsbW1. Using relevant mutant strains, RsfB was demonstrated to be the major anti-SigF antagonist in M. smegmatis. The phosphorylation state of Ser-63 was shown to determine the functionality of RsfB as an anti-SigF antagonist. RsbW2 was demonstrated to be the only protein kinase that phosphorylates RsfB in M. smegmatis. Phosphorylation of Ser-63 inactivates RsfB to render it unable to interact with RsbW1. Our comparative RNA sequencing analysis of the wild-type strain of M. smegmatis and its isogenic Δaa3 mutant strain lacking the aa3 cytochrome c oxidase of the respiratory electron transport chain revealed that expression of the SigF regulon is strongly induced under respiration-inhibitory conditions in an RsfB-dependent way.